Role of Red Sea trough on humidity source of east Mediterranean cyclones
Hkwe/;lkxjh; pØokr] fo’ks"k :i ls leqnz esa vkus okys iwohZ pØokr] bZjku esa ’khr _rq ds le; gksus okyh o"kkZ dh ?kVukvksa esa vR;ar egRoiw.kZ Hkwfedk fuHkkrs gSaA nwljh vkSj yky lkxj esa cuus okyh lrgh nzks.kh ds dkj.k m".kdfVca/kh; ks= ls vfr m".kdfVca/kh; ks= esa vknzZrk dk vilj.k gksrk gSA bZ- ,e- pØokrksa ds vknZzrk lzksrksa dh vkiwfrZ esa ykx lkxj dh Hkwfedk dk fu/kkZj.k djus ds fy, Hkw–foHko Å¡pkbZ ds lrg vk¡dM+ksa] mRrjh vkka’k ds 5 ls 65 fMxzh rd lhfer esa vkSj iwohZ ns’kkarj ds 0 ls 80 fMxzh esa iou dh fof’k"V vknzZrk vkSj m/okZ/kj rFkk kSfrt ?kVd dk mi;ksx fd;k x;k gSA bl v/;;u ds nkSjku Hkwe/; lkxj ds iwoZ esa 56 pØokrksa dh igpku dh xbZ tks yky lkxj ds nzks.kh ?kVukvksa ds ledkfyd FksA yky lkxj ds izcy nzks.kh ds ledkfyd pØokrksa ds 10 ekeyksa esa vknZz QyDl ds vfHklkjh ekufp= rS;kj fd, x,A pqfuank ekeyksa ds vknZZz QyDl ds vfHklkjh ekufp=ksa ds lR;kiu ls ;g irk pyk gS fd bZ- ,e- pØokrksa ds fy, visfkr dqN vknzZrk vjc lkxj ls vkjaHk gqbZ vkSj rRi’pkr Qkjl dh [kkM+h rFkk vnu dh [kkM+h esa dqN gn rd rks izcy jgh vkSj fQj yky lkxj ls xqtjrs gq, Hkwe/; lkxj ds nfk.k iwohZ ks= esa izos’k dj xbZA okLro esa yky lkxj bu pØokrksa ds vknZzrk lzksr esa dksbZ egRoi.wkZ Hkwfedk ugh fuHkkrk gS cfYd m".kdfVca/kh; ks= ls cfg m".kdfVca/kh; ks= dh vknzZrk ds vilj.k ds fy, ml ekxZ ls ek= xqtjus dh Hkwfedk fuHkkrk gS rFkk bZ- ,e- pØokrksa esa visfkr vknZzrk Hkj nsrk gSA mPp Lrjksa ij ty ds lD’ku dh ek=k vkSj mu LFkkuksa dk fu/kkZj.k djus ds fy, Hkw foksih vilj.k ds la;qDr ekufp=ksa vkSj /kzqoh; QzaV ds tsV izokgksa dk mi;ksx fd;k x;k gSA Mediterranean cyclones, especially east cyclones of this sea, play a very important role in precipitation events of cold season in Iran. In the other hand formation of surface trough over the Red Sea makes possible the displacement of humidity from tropical area to extra-tropical area. To determine the role of Red Sea trough in supplying humidity sources of EM cyclones, surface data of geopotential height, specific humidity and Vertical and Horizontal component of wind in limited 5 through 65 degrees of north latitude and 0 through 80 degrees of east longitude were used. During the study 56 cyclones formed over the east of Mediterranean recognized which were simultaneous to the Red Sea troughs events. Convergence maps of moisture flux of 10 cases of simultaneous cyclones with Red sea trough which were strong, were drawn. Verification of convergence maps of moisture flux of selected cases show some required humidity for EM cyclones are initiated from Arabian Sea and then to some extent are reinforced over Persian Gulf and Gulf of Aden and then by passing over Red Sea enter to the south east of Mediterranean Sea. Actually Red Sea has not an important role in the humidity source of these cyclones and acts as a pass way for displacement of humidity of tropical area to extra-tropical area and injects the required humidity into the EM cyclones. To determine the regions and the amount of suction in the high levels, composite maps of ageostrophic divergence and jet streams of polar front were used. , number=3, journal=MAUSAM, author=GHAEDI, S. and MOVAHEDI, S., year=2013, month=Jul., pages=539–546